Functional and radiological outcomes of posterior column tibial plateau fractures treated with column-specific fixation: a prospective study - Puneeth; B., Rajaneesh; Manjunath; R., Arun Kumar (International Journal of Research in Orthopaedics, 2025)
Background: Posterior column tibial plateau fractures are complex intra-articular injuries. This study aims to evaluate the functional and radiological outcomes of such fractures managed through column-specific open reduction and internal fixation based on CT classification. Methods: A prospective interventional study on 30 patients with posterior column tibial plateau fractures treated surgically between 2020 and 2022 at Deen Dayal Upadhyay Hospital, New Delhi. Fractures were classified based on CT imaging and approaches selected according to column involvement. Functional and radiological outcomes assessed at 6 months using Rasmussen’s grading systems. Data were analyzed using SPSS v21, with significance set at p<0.05. Results: Mean age of patients was 40.3±8.94 years, with a male predominance (86.67%). RTA accounted for 90% of injuries. Most common fracture pattern was PM/AM (33.33%), and the posteromedial approach was used in 60% of cases. The mean time to radiological union was 17.13±1.22 weeks. Functional outcomes were excellent in 33.33%, good in 60%, and fair in 6.67% of patients. Radiological outcomes showed excellent results in articular depression (63.33%), condylar widening (80%), and angulation (76.67%). A significant correlation was found between radiological and functional outcomes (p=0.030), but not between fracture classification and outcome (p=0.426). Minimal complications (4 superficial and 1 case of deep infection). Conclusion: CT-based classification and column-specific fixation of posterior tibial plateau fractures provides favorable functional and radiological outcomes with minimal complications. Accurate reduction and stable fixation tailored to fracture morphology are key to optimal recovery.